High-grade Adenocarcinoma of the Prostate Mimicking Urothelial Carcinoma is Negative for TERT Mutations. Issue 7 (August 2019) - Alaghehbandan, Reza; Vanecek, Tomas; Trpkov, Kiril; Comperat, Eva; Kristiansen, Glen; Svajdler, Marian; Cempirkova, Dana; Pavlovsky, Michal; Pivovarcikova, Kristyna; Stehlikova, Adela; Hora, Milan; Michal, Michal; et al.
Abstract : High-grade prostatic adenocarcinoma mimicking urothelial carcinoma (UC) is a rare and unusual variant, which can present a difficult diagnostic challenge. The aim of this study was to examine telomerase reverse transcriptase ( TERT ) mutations in order to improve differential diagnostic process in this scenario. Ten prostatic adenocarcinomas mimicking UC were retrieved by searching in-house and consultation files of Charles University Hospital, Plzen, Czech Republic, Tenon Hospital Paris, France, and University of Calgary, Canada. We performed microscopic slide review and immunohistochemical and molecular-genetic analyses using the available paraffin tissue. Patient age at diagnosis ranged from 44 to 86 years (mean, 71.8 y). All cases were transurethral resections, except one which was a prostate biopsy. Gleason score 5+5 was observed in 6 patients, whereas the remaining 4 had a Gleason score of 4+5. The tumors showed pseudopapillary, solid, nested, and cribriform architectural growth patterns. All cases were positive for prostatic markers including PSA, PAP, and NKX3.1. Immunohistochemical staining for urothelial marker, GATA3, was negative in 6 cases and only weakly positive in the remaining 4. All 10 cases showed no evidence of TERT mutations. We describe 10 high-grade prostatic adenocarcinomas that on morphology mimicked UC, but all demonstrated negative TERT mutations. A finding of negative TERT mutations in high-grade prostatic adenocarcinoma which mimics UC supports the notion that TERT promoter mutations are absent in prostate carcinoma, which may also aid the diagnostic work-up in difficult cases.